The lifestyle and nutritional factors for dry eye disease in depression population: a retrospective case–control study - Lee, Chia-Yi; Yang, Shun-Fa; Lian, Ie-Bin; Chang, Yu-Ling; Jhan, Yan-Ni; Chang, Chao-Kai (Frontiers in Medicine, 2024)
Background We aim to evaluate lifestyle and nutritional factors that lead to dry eye disease (DED) in a depressed population using data from the Taiwan BioBank (TWB). Methods A retrospective case–control study was conducted, and patients with depression based on a questionnaire were selected as the depression group. Each patient in the depression group was matched by age and sex to two individuals without depression, and a total of 3,754 and 7,508 patients constituted the depression and non-depression groups, respectively. Based on the questionnaire, the primary outcome was the presence of DED. Additionally, the chi-square test and interaction test were applied to survey the effect of lifestyle and nutritional factors on DED in the depression and non-depression groups. Results There were 822 (21.90%) and 958 (12.76%) DED patients in the depression and non-depression groups, respectively, and the incidence of DED was significantly higher in the depression group (p < 0.001). In terms of lifestyle and nutritional factors in the depression population, a higher rate of chronic pain and a sedentary lifestyle were observed than in the patients with depression without DED (both p < 0.05). According to the interaction test, the chronic pain (p = 0.0227) and sedentary lifestyle (p = 0.0002) were significant risk factors for DED presence in the depression group than in the non-depression group, while the persistent coffee consumption (p = 0.0005) and tea consumption (p = 0.0003) were significant protective factors for the DED exclusively for the depression group and not for the non-depression group. Conclusion The depression population could be significantly benefited from physical activity, coffee intake and tea intake regarding DED development compared to the general population.